2015
DOI: 10.1158/2159-8290.cd-14-1236
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring Genomic Alterations Define Major Subsets of KRAS-Mutant Lung Adenocarcinoma with Distinct Biology, Immune Profiles, and Therapeutic Vulnerabilities

Abstract: The molecular underpinnings that drive the heterogeneity of KRAS-mutant lung adenocarcinoma (LUAC) are poorly characterized. We performed an integrative analysis of genomic, transcriptomic and proteomic data from early-stage and chemo-refractory LUAC and identified three robust subsets of KRAS-mutant LUAC dominated, respectively, by co-occurring genetic events in STK11/LKB1 (the KL subgroup), TP53 (KP) and CDKN2A/B inactivation coupled with low expression of the NKX2-1 (TTF1) transcription factor (KC). We furt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
739
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 760 publications
(824 citation statements)
references
References 58 publications
43
739
4
5
Order By: Relevance
“…We and others previously demonstrated that molecular alterations commonly found in NSCLC have distinct effects on the therapeutic response to antineoplastic treatment regimens (7)(8)(9)(10). The recent study by Skoulidis and colleagues demonstrated that co-occurring genetic alterations in serine/threonine kinase 11/ liver kinase B1 (STK11/LKB1), TP53, and CDKN2A/B (cyclin-dependent kinase inhibitor 2A/B) characterize 3 major subgroups of KRAS-mutant lung adenocarcinoma (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others previously demonstrated that molecular alterations commonly found in NSCLC have distinct effects on the therapeutic response to antineoplastic treatment regimens (7)(8)(9)(10). The recent study by Skoulidis and colleagues demonstrated that co-occurring genetic alterations in serine/threonine kinase 11/ liver kinase B1 (STK11/LKB1), TP53, and CDKN2A/B (cyclin-dependent kinase inhibitor 2A/B) characterize 3 major subgroups of KRAS-mutant lung adenocarcinoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…The recent study by Skoulidis and colleagues demonstrated that co-occurring genetic alterations in serine/threonine kinase 11/ liver kinase B1 (STK11/LKB1), TP53, and CDKN2A/B (cyclin-dependent kinase inhibitor 2A/B) characterize 3 major subgroups of KRAS-mutant lung adenocarcinoma (10). KRAS/TP53 tumors were associated with higher levels of somatic mutations, inflammatory markers, and immune checkpoint effector molecules and improved relapse-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…Skoulidis et al [37] have defined three subsets of KRASmutant lung cancer with concurrent mutations in STK11/LKB1, TP53, and CDKN2A/B. These mutations are often acquired over time, especially with chemotherapy treatment.…”
Section: Implications Of Concurrent Mutationsmentioning
confidence: 99%
“…Additional prospective studies are required to further validate these findings. The CDKN2A/B subtype is associated with distinct pathological characteristics such as invasive mucinous histology, low TTF1 expression, and suppressed mTORC1 signaling [37].…”
Section: Implications Of Concurrent Mutationsmentioning
confidence: 99%
“…J Thorac Dis 2017;9(Suppl 13):S1364-S1372 jtd.amegroups.com to immune checkpoint blockade are lower in comparison with the double mutant tumors (47). KRAS mutations indicate a poor outcome of the patients and currently there is not any efficient targeted therapy for this disease (48).…”
Section: Introductionmentioning
confidence: 99%